Strategi Pembelajaran Tematik Berbasis Etnosains untuk Meningkatkan Kompetensi Sains dan Budaya Lokal - Indah Dwi Febrianti; Melva Zainil (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2025)
Thematic learning that integrates local wisdom through an ethnoscience approach is still not widely applied in elementary schools despite its great potential to improve understanding of science concepts while preserving local culture. This study aims to explore the implementation of ethnoscience-based thematic learning strategies and examine their impact on students’ science competence and understanding of local culture. Employing a qualitative research method with a case study approach, the study finds a significant improvement in students' comprehension of scientific concepts as well as an increased appreciation of local wisdom. This approach also enhances student engagement and motivation while encouraging teachers to implement contextual learning. Ethnoscience-based thematic learning has proven to be an effective strategy for integrating scientific and traditional knowledge in the elementary school curriculum.